Microbiota as a reservoir of antibiotic resistance genes: relevance and urgency - Naga Raju Maddela (Faculty of Medicine, Universitas Trisakti, 2026)
'Antimicrobial resistance' (AMR) is one of the top threats to global public health and developments.